EVALUATING PRIMARY CARE QUALITY MANAGEMENT CYCLE: A QUALITATIVE STUDY IN A WESTERN PART OF INDONESIA - Wardani, Elly; Nurhasanah, Nurhasanah; Hadi, Nurul; Kamil, Hajjul (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2023)
Introduction: Community health centers known in Indonesia as Primary Health Care (PHC) serve as the primary care facilities in the country. It is the main engine for the success of providing care at the first line for the community. Accreditation is among efforts to enforce a comprehensive management function in primary care. The achievement of accreditation reflects the management cycle of the PHC; however, a number of these facilities are still struggling with achieving maximum accreditation standards. Limited attention and research support that identify PHC management function called for further investigation. Therefore, this study initiated to investigate and evaluate the primary care management cycle and its functionality through the lens of qualitative research.Method: We conducted 15 in-depth interviews and one focus group discussion (FGD) which was attended by eight participants. The setting was in five PHC in Banda Aceh, the capital city of Aceh province, Indonesia. The involved participants were individuals who had a direct role in the accreditation process. The data was analyzed by using thematic analysis techniques.Result: There were three main themes and several subthemes derived from the analysis: (1) Work plan: integrative plan development, slow execution; (2) Leaders’ roles: Role’s awareness, work commitment. The results of this study evaluated the implementation of quality management in PHC. To some extent, there were potential obstacles for PHC hindering them from achieving optimal accreditation.Conclusion: These could create pathways for policy development or as a reference for related authorities/policymakers in developing a framework plan to assist the PHC in the implementation of the management cycle leading to plenary national acknowledgment.